2005
DOI: 10.1093/aob/mci160
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Genotypic Difference in Growth, Nutrient Accumulation and Ultrastructure in Response to Manganese and Iron Supply in Solution Culture

Abstract: The results confirmed the greater capacity of 'PI227557' for Mn and Fe accumulation than 'Biloxi' for most nutrient treatments. Hence, 'PI227557' may be a very useful genetic resource both in developing soybean cultivars for growth on low nutrient soils and in physiological studies to understand differing approaches to nutrient accumulation in plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 31 publications
3
31
1
1
Order By: Relevance
“…endoplasmatic reticulum were observed (Izaguirre-Mayoral and Sinclair, 2005), as well as in the mitochondria under Mn toxicity conditions (Santandrea et al, 1998). However, none of these effects were observed in the present study.…”
Section: Resultscontrasting
confidence: 80%
“…endoplasmatic reticulum were observed (Izaguirre-Mayoral and Sinclair, 2005), as well as in the mitochondria under Mn toxicity conditions (Santandrea et al, 1998). However, none of these effects were observed in the present study.…”
Section: Resultscontrasting
confidence: 80%
“…The highest decreasing was shown by MLGG 0025 that achieved 21.87%, while other genotypes had relatively low decreasing percentage. Some researcher also reported similar results, where increasing solution Mn concentration decreased shoot dry weight (Izaguirre-Mayoral & Sinclair, 2005;Khabaz-Saberi et al, 2009). Some genotypes did not experience seedling dry weigth decreasing.…”
Section: Figure 1 Root Length Of Soybean Germplasm In Control and Mnmentioning
confidence: 62%
“…For example, Sliman (1990) reported antagonism between Fe and Zn in soybean. Other studies have found that Fe reduced Mn concentrations in Indian mustard (Hamlin et al, 2008) and in soybean leaves (Izaguirre-Mayoral and Sinclair, 2005), but increased Mn concentrations in soybean shoots. Other authors reported a negative correlation between Zn and Cu (Pearson et al, 2008;Kumar et al, 2009).…”
Section: Resultsmentioning
confidence: 82%